The Effect of Giving Cow Manure and NPK Mutiara 16:16:16 Fertilizer on the Growth and Production of Lectuce (Lactuca sativa L.). - Rurin Ernawati, Noor Jannah, Akas PS . (Universitas 17 Agustus 1945 Samarinda, 2017)
The purpose of the research was to know the effect of cow manure and NPK Mutiara 16:16:16 fertilizer also the interaction for growth and production of the lectuce and to know the best dosage from cow manure and NPK Mutiara 16:16:16 from growth and production of lectuce.The research was conducted from April to June 2016, growing media until crops, and the experiment was carried in Mekar Jaya, Sumber Sari Village, Sebulu Subdistric of Kutai Kartanegara Regency, East Kalimantan Province. The research is using Randomized Block Design (RBD) which uses analysis factorial 4 x 4 and 3 replication. The first factor is application of cow manure (K) which consist of 4 levels dosage : without cow manure or control (k0), dosage cow manure 5 ton//ha or equa 25 g/polybag (k1), 10 ton/ha or equal 50 g/polybag (k2), 15 ton/ha or equal 75 g/polybag (k3) and the second factor is the NPK Mutiara 16:16:16 fertilizer (P) consisting of 4 levels : without NPK fertilizer (p0), dosage NPK 150 kg/ha or equal 0,75 g/polybag (p1), dosage NPK 300 kg/ha or equal 1,5 g/polybag (p2), dosage NPK 450 kg/ha or equal 2,25 g/polybag (p3).The result of the research showed that treatment of cow manure (K) significant effect plant height 21 days after planting, number of leaves 14 days and 21 days after planting. And then significantly a effect plant height 14 days and 28 days after planting, number of leaves 28 days after planting and fresh weight of the crop per plant. The highest fresh production obtained in treatment provision cow manure 75 g/polybag. or 15 ton/ha (k3) is 64,80 g/plant and the lowest fresh production obtained in treatment provision cow manure (k0) is 37,78 g/plant.Result of the research showed that application of NPK Mutiara 16:16:16 fertilizer doesn’t significant effect on height plant 14 days and 21 days after planting, number of leaves 14 days and 21 days after planting. Significant effect with plant height 28 days after planting And significantly effected plant height 28 days after planting and fresh weight of the crop per plant. The highest fresh production obtained in treatment provision dosage NPK fertilizer 2,25 g/polybag or 450 kg/ha (p3) is 59,94 g/plant and the lowest fresh production obtained in treatment provision without NPK Mutiara 16:16:16 or control (p0) is 45,29 g/plant.Interaction treatment of cow manure and NPK Mutiara 16:16:16 fertilizer doesn’t have significant effect plant height 14 days and 21 days after planting, number of leaves at age 14 and 21 days after planting. The significant effect with number of leaves 28 days after planting. Significantly effected plant height 28 days after planting and fresh weight of the crop per plant. The highest fresh weight of the crop is the treatment k3p3 (dosage cow manure 15 ton/ha and dosage NPK Mutiara 16:16:16 fertilizer 450 kg/ha), is 80,86 g/plant, and the lowest fresh production treatment is k0p0 (control treatment) is 38,60 g/plant.